Expression of RNA polymerase I catalytic core is influenced by RPA12. - Brittany L Ford; Ting Wei; Hester Liu; Catherine E Scull; Saman M Najmi; Stephanie Pitts; Wenjun Fan; David A Schneider; Marikki Laiho (PLoS ONE, 2023)
RNA Polymerase I (Pol I) has recently been recognized as a cancer therapeutic target. The activity of this enzyme is essential for ribosome biogenesis and is universally activated in cancers. The enzymatic activity of this multi-subunit complex resides in its catalytic core composed of RPA194, RPA135, and RPA12, a subunit with functions in RNA cleavage, transcription initiation and elongation. Here we explore whether RPA12 influences the regulation of RPA194 in human cancer cells. We use a specific small-molecule Pol I inhibitor BMH-21 that inhibits transcription initiation, elongation and ultimately activates the degradation of Pol I catalytic subunit RPA194. We show that silencing RPA12 causes alterations in the expression and localization of Pol I subunits RPA194 and RPA135. Furthermore, we find that despite these alterations not only does the Pol I core complex between RPA194 and RPA135 remain intact upon RPA12 knockdown, but the transcription of Pol I and its engagement with chromatin remain unaffected. The BMH-21-mediated degradation of RPA194 was independent of RPA12 suggesting that RPA12 affects the basal expression, but not the drug-inducible turnover of RPA194. These studies add to knowledge defining regulatory factors for the expression of this Pol I catalytic subunit.